Redefining the age of tattooing in western North America: A 2000-year-old artifact from Utah. (April 2019) - Gillreath-Brown, Andrew; Deter-Wolf, Aaron; Adams, Karen R.; Lynch-Holm, Valerie; Fulgham, Samantha; Tushingham, Shannon; Lipe, William D.; Matson, R.G.
Abstract: How people decorate their bodies provides insight into cultural expressions of achievement, group allegiances, identity, and status. Tattooing has been hard to study in ancient societies for which we do not have tattooed mummies, which adds to the challenge of placing current body modification practices into a long-term global perspective. Historic studies document the practice of tattooing among many Indigenous North American groups. While the distribution and complexity of tattoo traditions indicate these practices predate the fifteenth century CE and arrival of Europeans, the antiquity of North American tattooing is poorly understood. During a recent inventory of legacy archaeological materials from the Turkey Pen site in southeastern Utah, we discovered a tattooing implement constructed from a sumac stem, prickly pear cactus spines, and yucca leaf strips. This artifact was recovered in 1972 from an in situ midden but, until now, remained unidentified. The tattooing artifact dates to 79–130 CE during the Basketmaker II period (ca. 500 BCE – 500 CE), predating European arrival to North America by over 1400 years. This unusual tool is the oldest Indigenous North American tattooing artifact in western North America and has implications for understanding archaeologically ephemeral body modification practices. Events such as the Neolithic Demographic Transition—which occurs in many places around the globe—may link to an increase in body modification practices as social markers, as appears to be the case for the Basketmaker II people in the southwestern United States. Highlights: Discovery of an ancient tattooing artifact in a legacy collection from the United States Southwest. Artifact is the earliest tattooing evidence in the United States Southwest by a millennium. Human coprolites and maize cobs from the midden produced C 14 dates of 79–130 CE (2 σ). Experimental tattooing using cacti spines produces distinctive use-wear. Tattooing in the Neolithic Demographic Transition shows social dimensions of ancient body modification.